2003
DOI: 10.1097/01.inf.0000101188.95433.60
|View full text |Cite
|
Sign up to set email alerts
|

Childhood malaria in a region of unstable transmission and high human immunodeficiency virus prevalence

Abstract: HIV infection was associated with severe/complicated malaria, although the magnitude of the effect may be relatively small. Given that both malaria and HIV are widespread in Africa, even small effects may generate significant morbidity and mortality and major public health consequences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
44
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(50 citation statements)
references
References 15 publications
3
44
0
Order By: Relevance
“…IPT with SP must be given monthly in order to achieve the same improvements in birth weight as 8-12 weekly administrations in HIV-negative pregnant women. Compared with HIV-negative nonimmune patients, more severe malaria is seen in HIV-infected nonimmune patients, and severely immunocompromised HIV-infected patients in high-transmission settings have higher parasite densities (44,45). This suggests that the immunosuppression associated with HIV infection can affect the control of malaria-parasite numbers and would therefore compromise the effect of antimalarial immunity in reducing the selection and spread of antimalarial drug resistance.…”
Section: Hiv Infectionmentioning
confidence: 94%
“…IPT with SP must be given monthly in order to achieve the same improvements in birth weight as 8-12 weekly administrations in HIV-negative pregnant women. Compared with HIV-negative nonimmune patients, more severe malaria is seen in HIV-infected nonimmune patients, and severely immunocompromised HIV-infected patients in high-transmission settings have higher parasite densities (44,45). This suggests that the immunosuppression associated with HIV infection can affect the control of malaria-parasite numbers and would therefore compromise the effect of antimalarial immunity in reducing the selection and spread of antimalarial drug resistance.…”
Section: Hiv Infectionmentioning
confidence: 94%
“…Reported figures on the prevalence of malaria/HIV co-infections vary from one part of the country to another ranging from 29.4% in Douala, the economic capital [4] to 2.24% in Bamenda, the regional capital of the North West Region [5]. Some studies have suggested that repeated infections with malaria are associated with a rapid decline in CD4+ T lymphocytes over time while co-infections of malaria with HIV lead to more episodes of symptomatic [6] and even complicated malaria including death [7][8][9][10]. However, there is generally limited data on these aspects of malaria infection in HIV/AIDS patients in relation to CD4+ T lymphocyte count levels in Southwest Cameroon and such data is needed for proper control measures to be planned by health authorities.…”
Section: Introductionmentioning
confidence: 99%
“…Insecticide-treated bed nets (ITNs). Among people with HIV, malaria is more common and more severe (Grimwade, 2003;Whitworth, 2000), and may increase HIV viral load (Kublin 2005) and decrease CD4 cell count (Mermin, 2006b). …”
Section: Introductionmentioning
confidence: 99%